Necesidad de reformar la ley notarial para incorporar el sistema en línea que permita la obtención de copias de escrituras y su certificación en cualquier notaría pública - Loor Molina, Hilda Lucia (2014)
The Constitution of the Republic of Ecuador in art. 227 states that public administration is a service to the community which is governed by the principles of effectiveness, efficiency, quality, hierarchy, decentralization, decentralization, coordination, participation, planning, transparency and evaluation. This normative premise infers that all public authorities in Ecuador must manage their internal institutional processes in strict compliance with principles and rules governing the public sector, in order to properly promote response capabilities to meet the needs of citizens. Regarding notary services and the provision of their services Constitution establishes the important regulations such as determined in art. 199 mentions that are public and notary services in each county or metropolitan district will be the number of notaries and notaries determined by the Judicial Council. The problems identified part first establish that the Notarial Act did not incorporate reforms to promote agility and speed in managing internal processes and procedures relating to acts and contracts concluded before the notarial officer; from this perspective identifies the enabling legislation must implement changes to the recurrence information technology platforms and virtual information are considering electronic media that simplify the data collection information for those interested. In daily practice is a serious problem that people who want to obtain a certified copy of a public document held before the notary public must necessarily move to the notice of the canton where the act or contract was concluded, which implies a cost to the claimant, besides that the process becomes cumbersome for the time it takes to get the said certified copy; This situation can be remedied with the use of digital technologies, using the systematization of processes and notarial archives, through the generation of copies printed directly from data bases notarial work online, facilitating the direct taking of the information required by interested parties, thus promoting the true effectiveness and efficiency in the management of notary procedures.